Preparation method of water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristic

Through thermal injection synthesis and polar ligand exchange technology, the preparation process of copper-iron-sulfur CuFeS2 colloidal quantum dots is optimized, which solves the problems of poor dispersion and uneven size distribution in the existing methods, and realizes CuFeS2 colloidal quantum dots with water-soluble, uniform size and consistent crystal plane orientation, which is suitable for efficient preparation of optoelectronic devices.

CN119875615AInactive Publication Date: 2025-04-25SOUTH WEST INST OF TECHN PHYSICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411956626.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing copper-iron-sulfur CuFeS2 colloidal quantum dot preparation methods have problems such as poor dispersion, uneven size distribution and lack of clear crystal plane orientation, which limits its application in optoelectronic devices.

Method used

Copper-iron-sulfur colloidal quantum dots coated with non-polar ligands were synthesized by thermal injection, and water-soluble CuFeS2 colloidal quantum dots were obtained through polar ligand exchange. The raw materials, temperature, time and quantum dot surface ligands of the synthesis reaction were optimized, and CuFeS2 colloidal quantum dots were achieved uniform size, consistent crystal plane orientation, and good dispersion of aqueous solution.

Benefits of technology

It realizes the low-cost and efficient preparation of copper-iron sulfur CuFeS2 colloidal quantum dots, with uniform morphology, uniform size and narrow particle size distribution, and is suitable for photoelectric detection and photovoltaic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875615A_ABST
    Figure CN119875615A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a water-soluble copper-iron-sulfur colloidal quantum dot with near-infrared absorption characteristic, hexamethyldisilazane is used as a sulfur precursor, an organic sulfur source and an n-octadecene solvent can rapidly form a colloidal quantum dot nucleation site, and the nucleation and growth process of the quantum dot is controlled in stages. Therefore, the CuFeS2 colloidal quantum dot has a tetrahedral morphology and has a determined exposed crystal face. The CuFeS2 colloidal quantum dots prepared by the method are uniform in morphology, uniform in size and narrow in particle size distribution; the process is simple and easy to implement, synthesis equipment is low in price, molecular beam epitaxy equipment and the like required by a traditional semiconductor are not involved, and the method is very suitable for high-productivity preparation of colloidal quantum dots for photoelectric detection and photovoltaic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation and synthesis of colloidal quantum dots, and specifically relates to a method for preparing ternary copper-iron-sulfur CuFeS2 colloidal quantum dots which are water-soluble and have near-infrared absorption characteristics. Background Art

[0002] In recent years, as the information industry around the world develops towards high-quality and high-level fields, the information industry, which strongly relies on optoelectronic devices, has put forward higher requirements for optoelectronic materials, mainly including low cost of materials, environmental toxicity of materials and availability of materials. Among them, colloidal quantum dots have significant advantages in the field of optoelectronic display and optoelectronic detection, which are mainly reflected in their excellent optoelectronic properties and controllability. First, colloidal quantum dots have a size quantum confinement effect, which can adjust the luminescence wavelength according to the size of their particle size, and realize wide-band absorption and emission from the visible light to the infrared spectrum, which is suitable for a variety of display and detection needs. Secondly, colloidal quantum dots have the characteristics of high luminous efficiency and excellent color saturation, which enables them to present rich colors in display technology, improve display effects and color reproduction. It is particularly noteworthy that colloidal quantum dots that do not contain heavy metals have unique and outstanding contributions to the field of optoelectronic display and optoelectronic detection due to their environmental friendliness. Compared with traditional quantum dot materials containing toxic metals, colloidal quantum dots that do not contain toxic metals are safer and more reliable in terms of environmental ecology. Its low toxicity and biocompatibility make it have broad application prospects in the information industry, as well as in the biomedical field, biological imaging, fluorescent probes, etc. In addition, colloidal quantum dots that do not contain toxic metals also have better long-term reliability, which helps to extend the life of optoelectronic devices and improve their overall performance. In general, colloidal quantum dots that do not contain heavy metals have unique advantages in the fields of optoelectronic display and photoelectric detection. They provide new possibilities for the development of future optoelectronic device technology and show great application prospects and market prospects in the fields of biomedicine and ecological environmental protection.

[0003] Copper iron sulfur CuFeS2 colloidal quantum dots are a typical direct bandgap semiconductor material. The band width of the bulk material is 0.6eV. It has infrared absorption characteristics, the synthetic raw materials are easy to prepare and do not contain heavy metals. However, there are two major problems with the colloidal quantum dots synthesized by the current preparation methods of copper iron sulfur CuFeS2 colloidal quantum dots. First, the quantum dots synthesized by solvent thermal or high-temperature pyrolysis have poor colloid dispersion and uneven size distribution. They are prone to agglomeration and sedimentation in the solvent, which limits their practical use in optoelectronic devices. For example, Prashant Kumar et al. prepared wurtzite copper iron sulfur CuFeS2 colloidal quantum dots through aqueous phase synthesis in the early days (Chem. Commun., 2013, 49, 7316-7318), and the size distribution of quantum dots was extremely uneven; in addition, academic researchers such as Sujit D. Disale reported in their papers that the quantum dots prepared by high-temperature pyrolysis method were severely agglomerated (Appl. Organometal. Chem. 2009, 23, 492–497). Second, the copper iron sulfur CuFeS2 colloidal quantum dots obtained by the existing preparation method do not have a clear crystal plane orientation, and are usually irregularly spherical, which will hinder the carrier migration simulation of such quantum dots in optoelectronic devices. At the same time, the synthesis of quantum dots without a clear crystal plane orientation is usually considered to be caused by the immaturity of the preparation method. For example, in the preparation process of a preparation method for a ternary copper iron sulfur CuFeS2 fluorescent quantum dot with magnetic properties synthesized in an aqueous phase disclosed in CN105154060A, copper nitrate and ferric nitrate are dissolved in an alcohol solution to prepare CuFeS2 colloidal quantum dots. The quantum dots prepared by the method have irregular morphology and uneven size, and their fluorescence emission spectrum has a large half-peak width and irregular peak shape, which also explains the uneven size and morphology of the CuFeS2 colloidal quantum dots prepared by such methods. The current preparation method of CuFeS2 colloidal quantum dots seriously limits the application prospects of such materials in optoelectronic devices and the information industry. Summary of the invention

[0004] (I) Purpose of the invention

[0005] In order to solve the preparation problem of this type of colloidal quantum dots, the purpose of the present invention is to provide a method for preparing water-soluble copper, iron and sulfur colloidal quantum dots with near-infrared absorption characteristics, and to obtain low-cost CuFeS2 colloidal quantum dots with uniform size, consistent crystal orientation and good aqueous solution dispersibility by optimizing the raw materials, reaction temperature, reaction time and quantum dot surface ligands of the synthesis reaction, so as to improve the existing preparation process of CuFeS2 colloidal quantum dots.

[0006] (II) Technical solution

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics is provided, comprising hot injection synthesis to obtain copper-iron-sulfur colloidal quantum dots coated with non-polar ligands, and further obtaining water-soluble copper-iron-sulfur colloidal quantum dots by polar ligand exchange. Specifically, the following steps are included:

[0008] (1) Synthesis of non-polar ligand-coated copper-iron-sulfur colloidal quantum dots: In a 50 mL three-necked flask, cuprous iodide and ferric chloride were dissolved together in an oleylamine solution; heated under a continuous vacuum environment to remove air and water vapor; the atmosphere was replaced with nitrogen, and the temperature was continued to rise while maintaining a magnetic stirring state to obtain a copper-iron solution;

[0009] (2) dissolving hexamethyldisilathione in n-octadecene solvent to obtain a sulfur solution; slowly injecting the sulfur solution into the copper-iron solution obtained in step (1) through a syringe under continuous magnetic stirring; after the injection, keeping the mixture warm for 8 to 12 minutes, and cooling naturally to obtain a quantum dot CuFeS2 solution;

[0010] (3) taking the quantum dot CuFeS2 solution obtained in step (2), adding an equal volume of a 1:1 toluene-ethanol mixed solution, centrifuging and collecting the precipitate; washing the precipitate 2-3 times with a 1:1 toluene-ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots;

[0011] (4) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots: dissolve sodium sulfide nonahydrate in a mixed solution of dimethylformamide and water in a volume ratio of 3:1 to obtain a polar ligand exchange solution; dissolve the CuFeS2 colloidal quantum dots obtained in step (3) in cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; add the non-polar solution of CuFeS2 colloidal quantum dots to the polar ligand exchange solution, and continue magnetic stirring for 25 to 30 minutes to obtain a mixed solution; centrifuge the mixed solution to obtain a precipitate, and wash the precipitate with ethanol for 2 to 3 times to obtain water-soluble CuFeS2 colloidal quantum dots.

[0012] Furthermore, in step (1), the molar volume ratio of cuprous iodide, ferric chloride and oleylamine is 0.5-1.5 mmol: 0.5-1.5 mmol: 25-30 mL.

[0013] Furthermore, in step (1), the temperature of heating to remove air and water vapor under vacuum environment is 100°C, and the duration is 1-3 hours; the atmosphere is replaced with nitrogen and the temperature is continued to rise to 150-170°C.

[0014] Furthermore, in step (2), the molar volume ratio of hexamethyldisilathane to n-octadecene in the sulfur solution is 1.5-2.5 mmol: 2-4 mL.

[0015] Furthermore, in step (4), the mass volume ratio of sodium sulfide nonahydrate and dimethylformamide / water mixed solution in the polar ligand exchange solution is 100 mg:20 mL; the mass volume ratio of non-polar ligand-modified CuFeS2 colloidal quantum dots and cyclohexane in the non-polar solution of CuFeS2 colloidal quantum dots is 180-220 mg:8-12 mL.

[0016] The results of the present invention show that the water-soluble CuFeS2 colloidal quantum dots prepared by combining the hot injection method and the ligand exchange method have uniform size distribution. By controlling the types of metal precursors and sulfur precursors, CuFeS2 colloidal quantum dots with uniform morphology, uniform size, consistent crystal plane orientation, and good aqueous solution dispersibility can be prepared, and the raw material cost is low.

[0017] (III) Beneficial effects

[0018] The present invention has the following beneficial effects:

[0019] 1. Hexamethyldisilathione is used as a sulfur precursor, and the organic sulfur source can quickly form colloidal quantum dot nucleation sites with n-octadecene solvent, and the quantum dot nucleation and growth process are controlled in stages, so that the CuFeS2 colloidal quantum dots have the characteristics of consistent crystal plane orientation. The CuFeS2 colloidal quantum dots prepared by the present invention have uniform morphology, uniform size, and narrow particle size distribution.

[0020] 2. The process of the present invention is simple and easy, the synthesis equipment is inexpensive, and it does not involve equipment such as molecular beam epitaxy required for traditional semiconductors. There are no special requirements and it is very suitable for high-productivity preparation of colloidal quantum dots for photoelectric detection and photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Figure a is a low-magnification transmission electron microscopy image of the CuFeS2 quantum dots in Example 1; Figure b is a high-magnification transmission electron microscopy image of the CuFeS2 quantum dots in Example 1.

[0022] Figure 2 This is the UV-visible absorption diagram of CuFeS2 quantum dots in Example 1.

[0023] Figure 3 The size distribution statistics of CuFeS2 quantum dots prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown.

[0024] Figure 4 This is a picture of the colloidal quantum dot film formed by CuFeS2 quantum dots in Example 1. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0026] Embodiment 1:

[0027] The method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics in this embodiment comprises the following steps:

[0028] (1) Preparation of copper-iron solution: In a 50 mL three-necked flask, 1 mmol of cuprous iodide and 1 mmol of ferric chloride were dissolved in 28 mL of oleylamine; the mixture was heated to 100° C. for 2 h under continuous vacuum to remove air and water vapor; the atmosphere was replaced with nitrogen, and the temperature was continued to rise to 160° C. while maintaining magnetic stirring to obtain a copper-iron solution;

[0029] (2) Synthesis of copper iron sulfur colloidal quantum dots coated with non-polar ligands: 2 mmol of hexamethyldisilathane was dissolved in 3 mL of n-octadecene solvent to obtain a sulfur solution; the sulfur solution was slowly injected into the copper iron solution through a syringe under continuous magnetic stirring; after the injection, the reaction was kept warm for 10 minutes, and the solution was naturally cooled to obtain a quantum dot CuFeS2 solution; an equal volume of a 1:1 toluene ethanol mixed solution was added, and the precipitate was collected after centrifugation; the precipitate was washed 2-3 times with a 1:1 toluene ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots;

[0030] (3) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots: dissolve 100 mg of sodium sulfide nonahydrate in a mixed solution of 15 mL of dimethylformamide and 5 mL of water to obtain a polar ligand exchange solution; take 200 mg of the CuFeS2 colloidal quantum dots prepared in step (2) and dissolve them in 10 mL of cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; add the non-polar solution of CuFeS2 colloidal quantum dots to the polar ligand exchange solution, and continue magnetic stirring for 28 minutes to obtain a mixed solution; centrifuge the mixed solution and take out the precipitate, wash the precipitate with ethanol 2-3 times to obtain water-soluble CuFeS2 colloidal quantum dots.

[0031] Figure 1The transmission electron microscope image of the CuFeS2 colloidal quantum dots synthesized in Example 1 shows that the colloidal quantum dots are evenly dispersed, triangular in shape, and about 8 nanometers in size. Figure b shows the morphological characteristics and size of single-particle quantum dots more clearly. The single-particle electron microscope image of the CuFeS2 colloidal quantum dots is a triangular projection image, reflecting that the quantum dots are tetrahedral in shape, and their characteristic lattice fringes are (112) and (204) crystal planes, proving that the quantum dots are chalcopyrite crystal phases. These data show that the CuFeS2 colloidal quantum dots synthesized in Example 1 have a specific microscopic morphology and can expose specific crystal planes. Figure 2 is the ultraviolet-visible absorption spectrum of the quantum dots. From the figure, we can see that the absorption range of the quantum dots is 400-1000nm, the absorption range is wide, and it has the characteristics of near-infrared absorption.

[0032] Comparative Example 1:

[0033] A self-powered photoelectrochemical detector based on zinc-copper-indium-selenium-sulfur colloidal quantum dots and a preparation method thereof, wherein the preparation method comprises the following steps:

[0034] A method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics, the preparation method comprising the following steps:

[0035] (1) Preparation of copper-iron solution: In a 50 mL three-necked flask, 1 mmol of cuprous iodide and 1 mmol of ferric chloride were dissolved in 28 mL of oleylamine; the mixture was heated to 100° C. for 2 h under continuous vacuum to remove air and water vapor; the atmosphere was replaced with nitrogen, and the temperature was continued to rise to 160° C. while maintaining magnetic stirring to obtain a copper-iron solution;

[0036] (2) Synthesis of copper-iron-sulfur colloidal quantum dots coated with non-polar ligands: 2 mmol of sulfur powder was dissolved in 3 mL of n-octadecene solvent to obtain a sulfur solution; the sulfur solution was slowly injected into the copper-iron solution through a syringe under continuous magnetic stirring; after the injection, the reaction was kept warm for 10 minutes, and the solution was naturally cooled to obtain a quantum dot CuFeS2 solution; an equal volume of a 1:1 toluene-ethanol mixed solution was added, and the solution was centrifuged and precipitated; the precipitate was washed 2-3 times with a 1:1 toluene-ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots;

[0037] (3) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots: dissolve 100 mg of sodium sulfide nonahydrate in a mixed solution of 15 mL of dimethylformamide and 5 mL of water to obtain a polar ligand exchange solution; take 200 mg of the CuFeS2 colloidal quantum dots prepared in step (2) and dissolve them in 10 mL of cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; add the non-polar solution of CuFeS2 colloidal quantum dots to the polar ligand exchange solution, and continue magnetic stirring for 28 minutes to obtain a mixed solution; centrifuge the mixed solution and take out the precipitate, wash the precipitate with ethanol 2-3 times to obtain water-soluble CuFeS2 colloidal quantum dots.

[0038] Except for the different types of sulfur sources, Comparative Example 1 uses sulfur powder as the sulfur source, and the rest is the same as Example 1. Comparative Example 2:

[0039] A method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics, the preparation method comprising the following steps:

[0040] (1) Preparation of copper-iron solution: In a 50 mL three-necked flask, 1 mmol of cuprous iodide and 1 mmol of ferric chloride were dissolved in 28 mL of oleylamine; the mixture was heated to 100° C. for 2 h under continuous vacuum to remove air and water vapor; the atmosphere was replaced with nitrogen, and the temperature was continued to rise to 160° C. while maintaining magnetic stirring to obtain a copper-iron solution;

[0041] (2) Synthesis of copper iron sulfur colloidal quantum dots coated with non-polar ligands: 1 mmol of hexamethyldisilathane was dissolved in 3 mL of n-octadecene solvent to obtain a sulfur solution; the sulfur solution was slowly injected into the copper iron solution through a syringe under continuous magnetic stirring; after the injection, the reaction was kept warm for 10 minutes, and the solution was naturally cooled to obtain a quantum dot CuFeS2 solution; an equal volume of a 1:1 toluene ethanol mixed solution was added, and the solution was centrifuged and the precipitate was collected; the precipitate was washed 2-3 times with a 1:1 toluene ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots;

[0042] (3) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots: dissolve 100 mg of sodium sulfide nonahydrate in a mixed solution of 15 mL of dimethylformamide and 5 mL of water to obtain a polar ligand exchange solution; take 200 mg of the CuFeS2 colloidal quantum dots prepared in step (2) and dissolve them in 10 mL of cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; add the non-polar solution of CuFeS2 colloidal quantum dots to the polar ligand exchange solution, and continue magnetic stirring for 28 minutes to obtain a mixed solution; centrifuge the mixed solution and take out the precipitate, wash the precipitate with ethanol 2-3 times to obtain water-soluble CuFeS2 colloidal quantum dots.

[0043] Comparative Example 2 uses 1 mmol of hexamethyldisilathione as the sulfur source, and the rest is the same as Example 1 except that the amount of hexamethyldisilathione used is different.

[0044] Comparative Example 3:

[0045] A method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics, the preparation method comprising the following steps:

[0046] (1) Preparation of copper-iron solution: In a 50 mL three-necked flask, 1 mmol of cuprous iodide and 1 mmol of ferric chloride were dissolved in 28 mL of oleylamine; heated to 100 °C under continuous vacuum for 2 h to remove air and water vapor; replaced the atmosphere with nitrogen, continued to heat to 180 °C and maintained magnetic stirring to obtain a copper-iron solution;

[0047] (2) Synthesis of copper iron sulfur colloidal quantum dots coated with non-polar ligands: 2 mmol of hexamethyldisilathane was dissolved in 3 mL of n-octadecene solvent to obtain a sulfur solution; the sulfur solution was slowly injected into the copper iron solution through a syringe under continuous magnetic stirring; after the injection, the reaction was kept warm for 10 minutes, and the solution was naturally cooled to obtain a quantum dot CuFeS2 solution; an equal volume of a 1:1 toluene ethanol mixed solution was added, and the precipitate was collected after centrifugation; the precipitate was washed 2-3 times with a 1:1 toluene ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots;

[0048] (3) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots: dissolve 100 mg of sodium sulfide nonahydrate in a mixed solution of 15 mL of dimethylformamide and 5 mL of water to obtain a polar ligand exchange solution; take 200 mg of the CuFeS2 colloidal quantum dots prepared in step (2) and dissolve them in 10 mL of cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; add the non-polar solution of CuFeS2 colloidal quantum dots to the polar ligand exchange solution, and continue magnetic stirring for 28 minutes to obtain a mixed solution; centrifuge the mixed solution and take out the precipitate, wash the precipitate with ethanol 2-3 times to obtain water-soluble CuFeS2 colloidal quantum dots.

[0049] Except for the different reaction temperature, Comparative Example 3 uses 180°C to synthesize quantum dots, and the rest is the same as Example 1. Statistics of Size Distribution of CuFeS2 Colloidal Quantum Dots

[0050] The sizes of CuFeS2 colloidal quantum dots prepared by the above four synthesis methods were measured by transmission electron microscopy, and the size distribution of quantum dots was fitted, such as Figure 3 The size distribution displayed can obtain the average size and fitting parameters of the four CuFeS2 colloidal quantum dots. The results are shown in Table 1 below.

[0051] Table 1: Statistical parameters of colloidal quantum dot size distribution

[0052]

[0053] Based on the statistical parameters of colloidal quantum dot size distribution in Table 1, combined with Figure 3 It can be seen that the CuFeS2 colloidal quantum dots provided in Example 1 of the present application have excellent size distribution characteristics, and its standard deviation is only 0.26nm, which has a narrower size distribution than the other three types of comparative examples. The standard deviation of the colloidal quantum dots in Comparative Example 1 where the type of sulfur source is not optimized is 0.56nm, the standard deviation of the colloidal quantum dots in Comparative Example 2 where the sulfur source concentration is not optimized is 0.51nm, and the standard deviation of the colloidal quantum dots in Comparative Example 3 where the reaction temperature is not optimized is 0.46nm, which are all much larger than the standard deviation parameters of the colloidal quantum dots in Example 1. And the fitted half-peak width of the colloidal quantum dots in Example 1 is only 0.76nm, which is also much smaller than the other three types of comparative examples. The above results reflect that the patent of the present invention can obtain CuFeS2 colloidal quantum dots with uniform size distribution by optimizing the type of sulfur source, the concentration of sulfur source and the reaction temperature. Furthermore, by dripping the water-soluble CuFeS2 colloidal quantum dots in Example 1, the following can be obtained. Figure 4 The colloidal quantum dot film shown in the paper demonstrates the application potential of this type of quantum dots in thin-film devices such as detectors and light-emitting diodes.

[0054] In summary, the preparation method of water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics based on Example 1 provided by the present invention realizes water-soluble CuFeS2 colloidal quantum dots with uniform morphology, uniform size, narrow particle size distribution and near-infrared absorption through a low-cost solution synthesis process and a simple ligand exchange process, thereby solving the technical problems of difficult synthesis of such quantum dots, lack of specific morphology and wide size distribution.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing water-soluble copper-iron-sulfur colloidal quantum dots with near-infrared absorption characteristics, characterized in that: The following steps are involved: (1) Preparation of copper-iron solution; (2) Synthesis of copper iron sulfur colloidal quantum dots coated with non-polar ligands; (3) Ligand exchange to obtain water-soluble copper, iron and sulfur colloidal quantum dots.

2. The preparation method according to claim 1, characterized in that: In step (1), the copper-iron solution is prepared by: dissolving 0.5-1.5 mmol of a copper-containing compound and 0.5-1.5 mmol of an iron-containing compound together in 25-30 mL of an oleylamine solution; heating for 1-3 h under a continuous vacuum environment to remove air and water vapor; replacing the atmosphere with nitrogen, continuing to heat and maintaining a magnetic stirring state to obtain a copper-iron solution.

3. The preparation method according to claim 2, characterized in that: In step (2), the process of synthesizing the copper-iron-sulfur colloidal quantum dots coated with non-polar ligands is as follows: dissolving 1.5-2.5 mmol of a silicon-containing compound in 2-4 mL of an n-octadecene solvent to obtain a sulfur solution; slowly injecting the sulfur solution into the copper-iron solution through a syringe; after the injection is completed, keeping the reaction warm for 8-12 minutes, and naturally cooling to obtain a quantum dot CuFeS2 solution; adding an equal volume of a 1:1 toluene-ethanol mixed solution to the quantum dot CuFeS2 solution, centrifuging and collecting a precipitate; washing the precipitate with a 1:1 toluene-ethanol mixed solution to obtain non-polar ligand-modified CuFeS2 colloidal quantum dots.

4. The preparation method according to claim 3, characterized in that: In step (3), the process of ligand exchange to obtain water-soluble copper-iron-sulfur colloidal quantum dots is as follows: 80-120 mg of sodium sulfide nonahydrate is dissolved in a mixed solution of 18-22 mL of dimethylformamide and water to obtain a polar ligand exchange solution; CuFeS2 colloidal quantum dots are dissolved in cyclohexane to obtain a non-polar solution of CuFeS2 colloidal quantum dots; the non-polar solution of CuFeS2 colloidal quantum dots is added to the polar ligand exchange solution, and magnetic stirring is continued for 25 to 30 minutes to obtain a mixed solution; the mixed solution is centrifuged to obtain a precipitate, and the precipitate is washed with ethanol to obtain water-soluble CuFeS2 colloidal quantum dots.

5. The preparation method according to claim 4, characterized in that: In step (1), the copper-containing compound is cuprous iodide, the iron-containing compound is ferric chloride, the vacuum degassing heating temperature is 90-110°C, and the atmosphere is replaced with nitrogen and the heating temperature is continued to be 150-170°C.

6. The preparation method according to claim 5, characterized in that: In step (2), the silicon-containing compound is hexamethyldisilathane or sulfur powder.

7. The preparation method according to claim 6, characterized in that: In step (3), the volume ratio of the mixed solution of dimethylformamide and water is 3:

1.

8. The preparation method according to claim 7, characterized in that: In step (3), the mass volume ratio of non-polar ligand-modified CuFeS2 colloidal quantum dots and cyclohexane in the non-polar solution of CuFeS2 colloidal quantum dots is 180-220 mg: 8-12 mL.

9. The preparation method according to claim 8, characterized in that: In step (3), the mixed solution is centrifuged at a speed of 4000-6000 rpm, and the precipitate is washed 2-3 times.

10. A water-soluble copper-iron-sulfur colloidal quantum dot having near-infrared absorption characteristics obtained by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method for three-element copper-iron-sulfur (CuFeS2) fluorescent quantum dot with magnetic property by aqueous-phase synthesis

    CN105154060A

  • Near-infrared silver-copper-sulfur quantum dot and preparation method and application thereof

    CN112877062A

  • Preparation method of short-chain organic ligand modified PbS quantum dots, PbS quantum dot ink and application thereof

    CN118851253A

  • Sulfide-coated copper iron sulfide nanocrystals, and use thereof as photocatalysts for reduction of nitroaromatic compounds

    WO2022199724A1

  • A method of synthesizing quantum dots

    WO2024205502A1